Establishment of callus culture of aquilaria microcarpa baill - Rofiah, Binti Junaidi (Universiti Malaysia Sarawak (UNIMAS), 2012)
Aquilaria microcarpa Baill is a non–timber tree belongs to Thymeleaceae family. Gaharu is the valuable product produced by the tree. It is economically important. It can serve many purposes such as incense, fragrance and medicine. The study was carried out to establish an in vitro callus induction of A. microcarpa Baill. Leaf and petiole from 6 month old potted seedling were used and surface sterilized with 10%, 15% and 20% of Clorox for 10, 15 and 20 minutes plus Tween20 followed by Benomyl for 1 hour. In the study, 10% of Clorox concentration with 20 minutes exposure produced more axenic explant for leaf with 95% and petiole with 86.7%. Axenic leaf and petiole were placed into solidified MS media supplemented with different concentrations of 2,4–dichlorophenoxy acetic acid (2,4–D) alone at 0, 0.5, 1.0, 2.0 and 3.0 mg/L and also 2,4–D plus 0.5 mg/L of 6–benzylaminopurine (BAP) for callus induction. After 4 weeks of culture, leaf significantly produce 100% of callus while petiole with 73.3% success in media supplemented with 2.0 mg/l of 2,4–D plus 0.5 mg/l of BAP. Fully developed callus were subcultured after 4 weeks into fresh media to promote cell growth. The calli formed were transferred into MS media supplemented with Indole–3–butyric acid (IBA) and BAP for shoot proliferation. There was no shoot growth after 7 weeks of cultured, however, within week 4, calli cultured appeared light green in response to hormones applied. Therefore, further research needs to be continued for developing suitable and better plant regeneration protocol.